First Cases of Severe Flaccid Paralysis Associated With Enterovirus D68 Infection in Spain, 2015–2016. Issue 12 (December 2017) - Cabrerizo, María; García-Iñiguez, Juan Pablo; Munell, Francina; Amado, Alfonso; Madurga-Revilla, Paula; Rodrigo, Carlos; Pérez, Sonia; Martínez-Sapiña, Ana; Antón, Andrés; Suárez, Gerardo; Rabella, Nuria; del Campo, Víctor; et al.
Abstract : Enterovirus D68 was known to be the cause of mild to severe respiratory infections, but in the last few years, it has also been associated with myelitis and paralysis. This report describes the first Enterovirus D68 detections in acute flaccid paralysis cases occurring between December 2015 and March 2016 in Spain. Abstract : Supplemental Digital Content is available in the text.